Impact of Outsidered Children Status on Rights of Inheritance After Constitutional Court Decision - Sulaiman Sulaiman; Amin Purnawan (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
The objectives of this study are as follows: 1) To determine and explain the effect of the status of outsidered children status on the right to inherit after the Constitutional Court decision No. 46/PUU-VIII/2010 at the Kendari Religious Court. 2) To find out and explain the barriers to the status of outsidered children status against the right to inherit after the Constitutional Court decision No. 46/PUU-VIII/2010 at the Kendari Religious Court. 3) To find out and explain solutions to overcome the barriers to the status of children outside of marriage to the right to inherit after the Constitutional Court decision No. 46/PUU-VIII/2010 at the Kendari Religious Court. The method used by researchers is a sociological juridical legal approach and the specifications in this study include descriptive analytical. As for the sources and types of data in this study are primary data obtained from field studies with interviews with Religious Court Judges in Kendari City. And secondary data obtained from literature study. Based on the results of the research, in the case of inheritance after the decision of the constitutional court, the position of an outsidered children status as meant by the constitutional court decision of an outsidered children status is not the same as an adulterous child, has found a way or space to obtain recognition in order to protect the rights of outsidered children status. In this case the Constitutional Court ruled Article 46/PUU-VIII/2010 concerning children outside of marriage, having the right to recognition with their biological father and also entitled to an inheritance equal to the size of other children. Obstacles in this Constitutional Court Decision include the problem of the perspective of law enforcers and government officials to grant rights to children outside of marriage without different treatment or other discriminatory treatment. After providing solutions (or at least providing legal certainty) to outsidered children status born after the issuance of the Constitutional Court decision No. 46/PUU-VIII/2010 (curative), the Constitutional Court attempted with the Constitutional Court's decision to prevent the same cases from occurring.